Determination of dimethoate pesticide residues in water in the environment surrounding Lake Al-Sin (Journal of Hama University, 2024)
The research aimed to determine the concentration of the synthetic organophosphorous pesticide Dimethoate in the soils of the environment surrounding Lake Al-Sin during the extended period from December 2020 to June 2021. Soil samples were taken from two sites, one citrus and the other greenhouse. The study continued for seven consecutive months, the soil texture was determined and the organic matter was determined seasonally, and the pH - electric conductivity (EC), PO43- and humidity were measured. The herbicide analysis was carried out using high performance liquid chromatography (HPLC). The results showed the presence of dimethoate residues in the studied soil samples, with concentrations ranging between (4-34) mg.kg-1, and thus soil contamination with dimethoate was observed in the soil, and the highest concentrations were found in the greenhouse installation, as a result of the intensive use of dimethoate.
Keywords: Keywords: Organophosphate pesticides, Dimetoate, Al Sin spring basin, soil, HPLC